Anterior cingulate cortex, but not amygdala, modulates the anxiogenesis induced by living with conspecifics subjected to chronic restraint stress in male mice - Silveira, Lara Maria; Tavares, Ligia Renata Rodrigues; Baptista-de-Souza, Daniela; Carmona, Isabela Miranda; Carneiro de Oliveira, Paulo Eduardo; Nunes-de-Souza, Ricardo Luiz; Canto-de-Souza, Azair (Frontiers in Behavioral Neuroscience, 2023)
Cohabitation with a partner undergoing chronic restraint stress (CRE) induces anxiogenic-like behaviors through emotional contagion. We hypothesized that the anterior cingulate cortex (ACC) and the amygdala would be involved in the modulation of this emotional process. This study investigated the role of the ACC and amygdala in empathy-like behavior (e.g., anxiety-like responses) induced by living with a mouse subjected to CRE. Male Swiss mice were housed in pairs for 14 days and then allocated into two groups: cagemate stress (one animal of the pair was subjected to 14 days of restraint stress) and cagemate control (no animal experienced stress). 24 hours after the last stress session, cagemates had their brains removed for recording FosB labelling in the ACC and amygdala (Exp.1). In experiments 2 and 3, 24 hours after the last stress session, the cagemates received 0.1 µL of saline or cobalt chloride (CoCl2 1 mM) into the ACC or amygdala, and then exposed to the elevated plus-maze (EPM) for recording anxiety. Results showed a decrease of FosB labeling in the ACC without changing immunofluorescence in the amygdala of stress cagemate mice. Cohabitation with mice subjected to CRE provoked anxiogenic-like behaviors. Local inactivation of ACC (but not the amygdala) reversed the anxiogenic-like effects induced by cohabitation with a partner undergoing CRE. These results suggest the involvement of ACC, but not the amygdala, in anxiety induced by emotional contagion.